A polymorphism rs3746444 within the pre‐miR‐499 alters the maturation of miR‐499‐5p and its antiapoptotic function. Issue 11 (13th August 2018) - Ding, Wei; Li, Mengyang; Sun, Teng; Han, Di; Guo, Xiaoci; Chen, Xiao; Wan, Qinggong; Zhang, Xuejuan; Wang, Jianxun
Abstract: microRNAs (miRNAs) are non‐coding RNAs that function as post‐transcriptional regulators of cardiac development and cardiovascular diseases. Single nucleotide polymorphisms (SNPs) in miRNA genes are a novel class of genetic variations in the human genome that confer the risk of cardiovascular diseases. Here, we identified a polymorphism A→G (rs3746444) in miR‐499 precursor (pre‐miR‐499) that affects the maturation of miR‐499‐5p and alters its antiapoptotic function by converting stable A‐U base pair to wobble G‐U base pair in pre‐miR‐499 secondary structure. Furthermore, our results showed that the concentrations of plasma miR‐499‐5p could be correlated with myocardial infarction (MI) and heart failure (HF) patients in comparison with control subjects and polymorphism rs3746444 in miR‐499 could influence its abundance in plasma. Finally, our results also showed that the variant of polymorphism in miR‐499 influenced the severity of the myocardial infarction significantly. This is the first report to highlight the biological significance of this polymorphism on the maturation of miR‐499‐5p and its antiapoptotic role during MI. These findings may pave a way to better understand the individual variability based on miRNA SNPs in heart diseases and may contribute to better treatment for disease severity on a personalized level.